Study on Detection of the Bearing Stratum Integrity of Bored Pile Based on Transient Electromagnetic Method. (11th July 2022) - Pan, Chunwei; Zhang, Guocai; Chen, Sheng; Zheng, Fangkun; Liu, Xue
Abstract : To ensure the safe construction of bridge pile foundation in karst area, it is necessary to accurately detect the unfavorable geological conditions such as karst cave and soft layer before excavation. In this paper, the transient electromagnetic method is used to probe the geological conditions near the pile Y1 of an interworking main bridge in China's Hunan Province. By arranging 5 measuring lines at the pile Y1, the voltage variation laws of 21 monitoring points on each measuring line are obtained, and the resistivity variation cloud maps at the measuring line positions are inversed. The results show that the voltage signals at line 1 and line 5 are obviously abnormal, and the resistivity varies greatly within 50 m underground depth, which indicates that there may be adverse geological conditions such as karst cave and carbonaceous limestone interlayer. Further, through on-site hole digging and sampling, it is found that the slag sample in the area above 50 m of the stratum of pile Y1 is wet, and the slag sample below 50 m is dry without argillaceous interlayer, which verifies the effectiveness of transient electromagnetic detection method. Because the transient electromagnetic detection technology does not need drilling and the detection process is convenient, it may provide a new means for quickly detecting the integrity of the bearing layer of bored cast-in-place pile in bridge construction.